Learning objects (LOs) for mathematics - Žilinskienė, Inga (Lietuvos matematikos rinkinys, 2010)
This paper deals with LOs for mathematics of 11–12 class students. LOs from the national learning objects metadata repository have been selected. The discussion has been focused on three aspects: 1) how many LOs are there of 11–12 class students, search problems; 2) investigation of content provided in LOs; 3) investigation of interaction between learning content and students activities. It is found that LOs are poor in use of advanced interaction between content and students activities.
Keywords: learning object; learning objects for mathematics; learning objects repository; learning content; learning activities